Systematic Investigation of Plant-Parasitic Nematodes Associated with Main Subtropical Crops in Guangxi Province, China - Yi-Xue Mo (MDPI AG, 2021)
Plant parasitic nematodes (PPNs) are a pathogenic group that causes momentous crop yield loss by retarding plant growth and development through plant parasitization. In this study, the distribution of PPNs based on the main crops in Guangxi Province of China was investigated. A total of 425 samples of soil or roots from sugarcane, rice, maize, and soybean were collected in 68 counties, and a total of 48 order/family/genera of PPNs were identified, of which some genera were found in more than one crop. A total of 31 order/family/genera of PPNs were found in rice, among which Hirschmanniella was the most abundant, accounting for 79.23%, followed by Tylenchorhynchus (34.43%). Forty order/family/genera were observed in maize, of which the dominant genera were Pratylenchus and Tylenchorhynchus at 45.14% and 32.64%, respectively. In addition, 30 order/family/genera of PPNs were detected from sugarcane, and the percentages of Tylenchorhynchus and Helicotylenchus were 70.42% and 39.44%, respectively. The main crop of Eastern ecological regions was rice, with a high frequency of Hirschmanniella. The greatest frequency of Pratylenchus was found in the Western eco-region, which had a large area of maize. In the Northern eco-region, rice and maize were popular, with abundant Hirschmanniella and Helicotylenchus. In the Central eco-region, Pratylenchus was detected on the main crop of sugarcane. Hirschmanniella (72.94%) was dominant in clay, and Tylenchorhynchus (54.17%) showed the highest frequency in loam. The distribution of PPNs varied with different altitudes. The diversity of this phenomenon was closely related to host plants. These results could improve understanding of the distribution of PPNs and provide important information for controlling PPNs.